Evaluating force distributions within virtual uncemented mine backfill using discrete element method - Alsidqi, B.Mahmud Hasan; Ali, Karrech; Bruno, Chareyre (American Society of Civil Engineers (ASCE), 2017)
This paper investigates the distribution of intergranular forces within uncemented mine backfills using the discrete element method (DEM) and compares it with the existing analytical method. The virtual backfilling is modeled via the DEM to simulate the underground mining stopes backfilling with uncemented granular materials. Normal and shear forces of all particle contacts within the model backfill are tracked and analyzed with particular attention to the effect of sidewall friction. The DEM evaluates normal force chains and reveals a concentration of high forces within the model backfill. The DEM shows profiles of forces that are distinctly different from those obtained from analytical solutions. Quantitative analyses of the spatial distribution of forces, number of contact points, and changes in the orientation of forces are presented. The DEM demonstrates its capacity as a good tool for looking closely into the backfill on a particle scale. It highlights potential force distribution and concentration within a backfill and shows the limitations of analytical solutions, which helps engineers in the mining industry to better understand the possible mechanisms within backfill.